Refugee Migration and Health Challenges for Germany and Europe - Krämer, Alexander; Fischer, Florian; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book focuses on the closely interlinked areas of refugee migration and health. It discusses the main challenges of the recent unprecedented, extremely diverse and mostly unregulated refugee migration wave for Germany and Europe, and offers a broader view of refugee health from a European perspective. Health issues can lead to several challenges for refugees as well as healthcare providers, and as such the book also examines the requirements for the management of migrant populations in terms of medical care and health system adaptations, and includes theoretical aspects of refugee migration and health as well as various perspectives on the latest developments. Lastly, it describes the healthcare system demands and responses for short- and long-term care of refugees.
Part 1: Theoritical Foundations and Recent Developments -- 1. Refugee Health: Public Health theory and Disease Dynamics -- 2. Overview of Migration and Health in Europe -- 3. Social Transformation(s): International Migration and Health -- 4. Migrants, Refugees, Asylum Seekers: Use and Misuse of Labels in Public Health Research -- 5. Mental Health Enables Integration: Re-thinking Treatment Approaches for Refugees -- Part 2: Refugee Health in Germany: Healthcare System Demands and Responses -- 6. Screening for Infectious Diseases on Arrival and Integrated Healthcare for Refugees and Asylum Seekers during the First Months after Arrival -- 7. The Building of Structures for Acute Care, Initial Medical Screening, and Vaccination Prevention for Refugees in the State of Berlin - Challenges and New Concepts -- 8. German Public Health Services and Refugee Health: Overview of Current Experiences of Healthcare in Bavaria -- 9. Health Status and Disease Burden of Unaccompanied Asylum Seeking Adolescentsat a Single Centre in Bielefeld -- 10. Future Challenges for the Public and Curative Health Sector. Part 3: European Perspective on Refugee Health -- 11. Migrants' Health Protection: Socio-health and Legal Situation of Asylum Seekers and Refugees in Italy -- 12. The Challenge of a Comprehensive Health Response to the Refugee Crisis in Greece -- 13. Healthcare for Refugees in the Netherlands: The Stepped-care Model -- 14. Refugees and Health in Switzerland -- 15. Refugee and Migrant Health: A Perspective from Sweden -- 16. Challenges in Meeting the Mental Health and Wellbeing Needs of Refugee Children and Young People in England: Evaluation and Critique of Policy and Guidance -- Part 4: Conclusion -- 17. Conclusion: Roadmap for Refugee Health.
Keywords: Emigration and immigration; Public health; Human Migration; Public Health